Indoxyl sulfate associates with cardiovascular phenotype in children with chronic kidney disease - Holle, Johannes; Querfeld, Uwe; Kirchner, Marietta; Anninos, Alexandros; Okun, Jürgen G.; Thurn-Valsassina, Daniela; Bayazit, Aysun; Niemirska, Ana; Canpolat, Nurhayat; Bulut, Ipek Kaplan; Düzova, Ali; Anarat, Ali; et al. (Pediatric nephrology, 2019)
Cardiovascular disease is the leading cause of death in children with chronic kidney disease (CKD). Serum levels of gut-derived uremic toxins increase with deterioration of kidney function and are associated with cardiac comorbidities in adult CKD patients.
Gesehen am 30.04.2020